Acute kidney injury following coronary revascularization procedures in patients with advanced CKD. Issue 11 (9th July 2018) - Gaipov, Abduzhappar; Molnar, Miklos Z; Potukuchi, Praveen K; Sumida, Keiichi; Szabo, Zoltan; Akbilgic, Oguz; Streja, Elani; Rhee, Connie M; Koshy, Santhosh K G; Canada, Robert B; Kalantar-Zadeh, Kamyar; Kovesdy, Csaba P
Abstract: Background: Previous studies reported that compared with percutaneous coronary interventions (PCIs), coronary artery bypass grafting (CABG) is associated with a reduced risk of mortality and repeat revascularization in patients with mild to moderate chronic kidney disease (CKD) and end-stage renal disease (ESRD). Information about outcomes associated with CABG versus PCI in patients with advanced stages of CKD is limited. We evaluated the incidence and relative risk of acute kidney injury (AKI) associated with CABG versus PCI in patients with advanced CKD. Methods: We examined 730 US veterans with incident ESRD who underwent a first CABG or PCI up to 5 years prior to dialysis initiation. The association of CABG versus PCI with AKI was examined in multivariable adjusted logistic regression analyses. Results: A total of 466 patients underwent CABG and 264 patients underwent PCI. The mean age was 64 ± 8 years, 99% were male, 20% were African American and 84% were diabetic. The incidence of AKI in the CABG versus PCI group was 67% versus 31%, respectively (P < 0.001). The incidence of all stages of AKI were higher after CABG compared with PCI. CABG was associated with a 4.5-fold higher crude risk of AKI {odds ratio [OR] 4.53 [95% confidence interval (CI) 3.28–6.27]; P < 0.001}, which remained significant after multivariable adjustments [OR 3.50 (95% CI 2.03–6.02); P < 0.001]. Conclusion: CABG was associated with a 4.5-fold higher risk of AKI compared with PCI in patients with advanced CKD. Despite other benefits of CABG over PCI, the extremely high risk of AKI associated with CABG should be considered in this vulnerable population when deciding on the optimal revascularization strategy.